2014
DOI: 10.1371/journal.pone.0111172
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of Insertion Site Flanking Sequence and Construction of Transfer DNA Insert Mutant Library in Stylosanthes Colletotrichum

Abstract: Stylosanthes sp. is the most important forage legume in tropical areas worldwide. Stylosanthes anthracnose, which is mainly caused by Colletotrichum gloeosporioides, is a globally severe disease in stylo production. Little progress has been made in anthracnose molecular pathogenesis research. In this study, Agrobacterium tumefaciens-mediated transformation was used to transform Stylosanthes colletotrichum strain CH008. The major factors of the genetic transformation system of S. colletotrichum were optimized a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The identification of important pathogenicity genes (Zhao et al ., ; Fang et al ., ) and a new fungal pigmentation gene cluster (in this study), further confirm the utility of the library for identifying genes involved in important biological processes. However, results with DNA insertion library projects (Jeon et al ., ; Chen et al ., ; Michielse et al ., ), require follow up experiments to validate associations of phenotypes of the mutants with the disrupted genes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The identification of important pathogenicity genes (Zhao et al ., ; Fang et al ., ) and a new fungal pigmentation gene cluster (in this study), further confirm the utility of the library for identifying genes involved in important biological processes. However, results with DNA insertion library projects (Jeon et al ., ; Chen et al ., ; Michielse et al ., ), require follow up experiments to validate associations of phenotypes of the mutants with the disrupted genes.…”
Section: Discussionmentioning
confidence: 98%
“…Studies with plant pathogenic fungi such as Magnorporthe oryzae , Fusarium oxysporum and Stylosanthes colletotrichum have shown that a large DNA insertion mutant library is a very useful tool for identifying pathogenicity loci (Jeon et al ., ; Chen et al ., ; Chen et al ., ; Michielse et al ., ). We developed an efficient Agrobacterium ‐mediated transformation method for M. robertsii (Fang et al ., ), and used it to construct a T‐DNA insertion library with more than 20,000 transformants.…”
Section: Introductionmentioning
confidence: 98%
“…Colletotrichum gloeosporioides is a hemibiotrophic fungal pathogen which causes lesions on leaves, stems, fruits and other parts of woody or herbaceous plant [ 4 , 5 , 6 ]. Anthracnose caused by C. gloeosporioides is one of the most destructive and predominant diseases of stylo worldwide, greatly limiting the yield of stylo [ 7 ]. Typical symptoms of stylo anthracnose are spreading irregular lesions in leaves with dark margins and light brown centers, which spread to all tissues during the late stage of the disease [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the released DNA fragment flanked by the T-DNA arms inserts into the host genome in a random manner 24 26 . Indeed, it is based on this feature, AMT has been used to generate mutant library for microbes 27 , 28 .…”
Section: Introductionmentioning
confidence: 99%